Letter (copy) : Relief work for Spain - Citrine, Walter, 1887-1983
028-0078-001 WMC/HVT/FC/464. Secretary's. 23rd January, 1937. Mr. D. Darling, Generalitat De Catalunya, 3, Victoria Street, LONDON, S.W.1. Dear Mr. Darling, RELIEF WORK FOR SPAIN. Many thanks for your letter of the 22nd instant and for your kind offer of assistance. Arrangements in connection with the hospital will, of course, be made through our Joint International Committee which usually meets in Paris and, as you will probably see from my article, Mr. Schevenels is in charge of a convoy of lorries which will have passed through Catalonia, and I think that either on his outward or return journey he will take the opportunity of meeting such people as are necessary to facilitate the work. Nevertheless, I am obliged for your offer and should occasion arise I will certainly keep it in mind. Yours sincerely, General Secretary. 292/946/28/78